Neurotechnology for Special Needs Children - Fauzan, Norsiah (European Journal of Social Science Education and Research, 2015)
This paper highlights the use of neurotechnology to improve the brain dysregulation of special needs children giving an example of a case study on autistic children. Neurofeedback Training (NFT) was preceded by objective assessment of brain activity using Quantitative electroencephalogram (qEEG) to identify the abnormalities of the childrens’ brain waves. Neurofeedback training were conducted based on relevant EEG findings in relation to the children’s medical history and symptoms. Analysis indicate excessive presence of delta wave at the Frontal lobes and posterior regions. NFT were conducted within three months for more than 25 sessions for each protocol starting with Beta training followed by Delta and Alpha protocols. The observations and assessment showed improvement in terms of social interaction and communication and increased Alpha-beta activity in some parts of the brain suggesting improvement in brain regulation.
Keywords: Neurotechnology, Special needs education, Autism